Utilization of e-commerce in increasing the marketing of home industrial products in Cirebon district - Noval Maliki; Amiruddin (Peneliti Teknologi Teknik Indonesia, 2023)
The rapid development of technology and information requires people to get to know the internet. One of the new lifestyles that was born is shopping via the internet or often called e-commerce. The use of e-commerce is not only carried out by large companies, but also by micro, small and medium enterprises (MSMEs). This service is carried out to find out the use of e-commerce in order to increase the competitiveness of MSMEs in Kebarepan Village, Plumbon District, Cirebon Regency. The method used is a qualitative method with a participatory approach. Determination of this sample using purposive sampling technique. The results show that the use of e-commerce will be able to increase the income of MSMEs, the products marketed will be easily recognized by consumers making it easier to get customers. In addition, the use of e-commerce can save promotion costs and increase transaction speed. This will ultimately increase the competitiveness of MSMEs in Kebarepan Village, Plumbon District, Cirebon Regency.